PENEGAKAN HUKUM PERATURAN DAERAH KABUPATEN SUKABUMI NOMOR 4 TAHUN 2019 TENTANG KAWASAN TANPA ROKOK DALAM ANGKUTAN UMUM - Reinaldy Rodiana Dachlan; Agus Rasyid Chandra Wijaya (INTELIGENSIA MEDIA, 2024)
A Non-Smoking Area is a space or area declared to be prohibited for all activities related to smoking such as consuming, producing, selling, advertising, and./or promoting tobacco products. Meanwhile, law enforcement is a series of real actions taken to execute the function of legal norms. This study aims to understand how the law enforcement of Sukabumi Regency Regional Regulation Number 4 of 2019 concerning Non-Smoking Areas in Public Transport is implemented. The type of research conducted is empirical juridical, which is legal research on the application or implementation of normative legal provisions in action in each specific legal event that occurs in the community. This research was conducted at the office of the Civil Service Police Unit of Sukabumi Regency and the Office of the Health Service of Sukabumi Regency. Data collection techniques used interviews and questionnaires. From this Study, it can be concluded that in terms of Lawrence M. Friedman’s Legal System Theory, the enforcement of Sukabumi Regency Regional Refulation Number 4 of 2019 concerning Non-Smoking Areas in Public Transport is “Not Effective” due to several factor that hinder law enforcement implementation by law enforcement officers such as human resources, facilities, financial resources and the legal culture of the community which is not yet good.